Clinical effectiveness of cognitive therapy v. interpersonal psychotherapy for depression: results of a randomized controlled trial. Issue 10 (July 2015) - Lemmens, L. H. J. M.; Arntz, A.; Peeters, F.; Hollon, S. D.; Roefs, A.; Huibers, M. J. H.
<x content-type="archive" xml:space="preserve">Abstract</x> Background Although both cognitive therapy (CT) and interpersonal psychotherapy (IPT) have been shown to be effective treatments for major depressive disorder (MDD), it is not clear yet whether one therapy outperforms the other with regard to severity and course of the disorder. This study examined the clinical effectiveness of CT v. IPT in a large sample of depressed patients seeking treatment in a Dutch outpatient mental health clinic. We tested whether one of the treatments was superior to the other at post-treatment and at 5 months follow-up. Furthermore, we tested whether active treatment was superior to no treatment. We also assessed whether initial depression severity moderated the effect of time and condition and tested for therapist differences. Method Depressed adults (n = 182) were randomized to either CT (n = 76), IPT (n = 75) or a 2-month waiting list control (WLC) condition (n = 31). Main outcome was depression severity, measured with the Beck Depression Inventory – II (BDI-II), assessed at baseline, 2, 3, and 7 months (treatment phase) and monthly up to 5 months follow-up (8–12 months). Results No differential effects between CT and IPT were found. Both treatments exceeded response in the WLC condition, and led to considerable improvement in depression severity that was sustained up to 1 year. Baseline depression severity did not moderate the effect of time and condition. Conclusions Within our power and time ranges, CT and IPT appeared not to differ in the treatment of depression in the acute phase and beyond.